1997
DOI: 10.1183/09031936.97.10071467
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between allergic manifestations and Toxocara seropositivity: a cross-sectional study among elementary school children

Abstract: Toxocara (the cause of visceral larva migrans in humans) and allergy have in common both elevated immunoglobulin E (IgE) levels and eosinophilia. In the present study, we investigated: 1) associations between Toxocara seropositivity and allergic manifestations; 2) risk factors for Toxocara infection; and 3) differences in Toxocara seroprevalence, allergic manifestations and the associations between these two, in children from urban and rural environments.Blood samples from 1,379 Dutch urban and rural elementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
3
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 26 publications
13
76
3
16
Order By: Relevance
“…Although IgG antibodies are useful for toxocariasis diagnosis, this cannot be considered as a marker for cure of the disease because titres can remain elevated for several years after treatment 19,28 . BUJS et al 4 observed a positive association between asthma, anti-Toxocara spp. antibodies and inhaled allergens such as D. pteronyssinus.…”
Section: Discussionmentioning
confidence: 99%
“…Although IgG antibodies are useful for toxocariasis diagnosis, this cannot be considered as a marker for cure of the disease because titres can remain elevated for several years after treatment 19,28 . BUJS et al 4 observed a positive association between asthma, anti-Toxocara spp. antibodies and inhaled allergens such as D. pteronyssinus.…”
Section: Discussionmentioning
confidence: 99%
“…also had increased IgE levels and skin allergenic reactivity associated mainly with clinical manifestations and inhalant aeroallergens 11 . However, BUIJS et al 3 explains that Toxocara spp. may stimulate allergic asthma and atopic manifestations due to a hereditary mechanism that distorts type 2 T-helper cell function, promoting parasite host longevity through the increase of an allergen-specific and Toxocara-specific IgE.…”
Section: Discussionmentioning
confidence: 99%
“…; ADAMI, C.; FALAVIGNA-GUILHERME, G.; RUBINSKY-ELEFANT, G. & FALAVIGNA-GUILHERME, A.L. reported in toxocariasis by many authors 3,8,25 . In this study six patients had increased levels of IgE, and in five out of seven cases breathlessness was reported as the main complaint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical manifestations in humans vary with the species of parasite, but include visual 21 , neurological 15 , dermatological 14 , respiratory 3 , and enteric 11 involvement, and there is a further impact on public health and economy 23 . A study to determine the prevalence of each parasite is necessary for the development of appropriate preventive and control measures.…”
Section: Introductionmentioning
confidence: 99%